If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(-4u+5)-4u=2(u-3)-6
We move all terms to the left:
-3(-4u+5)-4u-(2(u-3)-6)=0
We add all the numbers together, and all the variables
-4u-3(-4u+5)-(2(u-3)-6)=0
We multiply parentheses
-4u+12u-(2(u-3)-6)-15=0
We calculate terms in parentheses: -(2(u-3)-6), so:We add all the numbers together, and all the variables
2(u-3)-6
We multiply parentheses
2u-6-6
We add all the numbers together, and all the variables
2u-12
Back to the equation:
-(2u-12)
8u-(2u-12)-15=0
We get rid of parentheses
8u-2u+12-15=0
We add all the numbers together, and all the variables
6u-3=0
We move all terms containing u to the left, all other terms to the right
6u=3
u=3/6
u=1/2
| 10x+25x-3)=275 | | 22.36+473c=64.83 | | 22.36+473c=64+93 | | 0.13x+0.3(x-2)=0.01(2x-4) | | 7a+50+14a-20=90 | | 6x-x-3x=3x+12 | | 10x+(250x-75)=275 | | 5z+36=-7z | | 1.5(2p+4)=6+3p | | 47=-19+x | | 11w+2(w+10)=5w-6 | | 27=4r−5 | | 4x-8=16x-32 | | 9x+17=10x+6 | | -10.80=2.8a | | -2.4-3x=11.1 | | 13k+-4=4 | | 2(x+3)+4x=3x | | 36x-12=14x+56 | | 3x-10=11-4x | | 3y-24=-2(y-3) | | -2-5(2x-1)=3(6-2x) | | 50v=5 | | 9x-7=5+5x | | S=s+6/5 | | 3y-24=2(y-3) | | 2(x÷4)=2x+5 | | 3.25x(-0.4)=3 | | 25/b=39/9 | | 5=-w/6+2 | | (4x-1)+(2x-1)=(5x) | | 8=x÷2 |